2017
DOI: 10.4236/oalib.1104184
|View full text |Cite
|
Sign up to set email alerts
|

Combustion and Emission Analysis of SI Engine Fuelled by Saudi Arabian Gasoline RON91 and RON95 with Variable Compression Ratios and Spark Timing

Abstract: The performance, emissions and combustion characteristics of a spark ignition engine at varying compression ratio and spark timing using two grades of gasoline in Saudi Arabian market, RON91 and RON95 have been presented on this paper. The tests were conducted using a single cylinder, four-stroke spark ignition research engine that operates with different RON fuel. The experiments were conducted at a wide-open throttle with an engine speed of 2500 rpm at stoichiometric conditions for three different compressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Brake thermal efficiency is a dimensionless measure of the engine's thermal performance divided by the total units of heat in the fuel burned. The following equation may be used to calculate thermal efficiency [9], [20]:…”
Section: Machine Performance Testmentioning
confidence: 99%
“…Brake thermal efficiency is a dimensionless measure of the engine's thermal performance divided by the total units of heat in the fuel burned. The following equation may be used to calculate thermal efficiency [9], [20]:…”
Section: Machine Performance Testmentioning
confidence: 99%
“…If the spark occurs too quickly, the piston will be slowed in its upward motion. On the other hand, if the spark is delayed, the piston will move downwards, so in both cases, the work done on the piston will be reduced [5].…”
Section: Volume 21 (2) 2022mentioning
confidence: 99%
“…The ratio of the maximum piston volume to the minimum compressed volume is called the compression ratio. Varying compression ratios offer a diverse potential of combustion efficiency, which can be translated to torque and horsepower under varying loads and speed conditions [13,14]. The compression ratio is defined as the difference between the volume in the combustion chamber above the piston when the piston is at the bottom dead centre (BDC) to the piston at the top dead centre (TDC) [15].…”
Section: Compression Ratiomentioning
confidence: 99%
“…There are many causes of pre-ignition and one of them is the type of fuel used in the experiment. Binjuwair et al [14] found that in comparing between RON 95 and RON 91, RON 91 showed better performance by 0.54 % at a compression ratio of 10.5:1. In this experiment, only fuel type…”
Section: Power and Torque For Low And High Compression Pistonmentioning
confidence: 99%